Nonoperative treatment of avulsion fracture of the anterior tibia with proximal fibular fracture: A case report - Yu, Jian; Zhang, Chao; Wang, Xu; Ma, Xin; Huang, Jiazhang (Frontiers in Surgery, 2023)
Background: Avulsion fracture of the anterior tibia with proximal fibular fracture commonly occurs in Maisonneuve fracture which generally involves ankle instability and requires surgical correction. Non-operative Treatment of this type of fracture has been rarely reported in the literature Case presentation: A forty-eight-year-old male reported pain in the lateral part of his left lower leg and ankle during a badminton play. Physical examination revealed tenderness and swelling of the medial and lateral aspects of the left ankle, as well as the proximal aspect of the fibula. Pre-operative plain X-ray image, Computed Tomography (CT), and Magnetic Resonance Imaging (MRI) revealed an avulsion fracture of the anterior tibia by the anterior tibiofibular ligament without fracture of the medial and posterior fracture and rupture of the deltoid ligament and interosseous membrane. Non-operative management was performed and successful recovery was observed at a 6-month follow-up. Conclusions: Non-operation management can be a better option for some variations of Maisonneuve fracture with a stable tibiotalar joint. The selection of treatment options should be based on careful examination and radiological evaluation of the ankle.